PENERAPAN MEDIA AUDIO VISUAL SEBAGAI UPAYA MENINGKATKAN MINAT BELAJAR SISWA SD INPRES NDETUWARU - Yuliana Yenita Mete; Jumilah Gago; Melkianus Bernadin Lalong (LPPM Universitas Cipta Mandiri, 2025)
The study subjects were 10 fourth-grade students, consisting of 6 boys and 4 girls. Data collection techniques included observation, interviews, documentation, and a questionnaire measuring four indicators of learning interest: enjoyment, interest, attention, and student engagement in learning. The results showed an increase in student interest in learning after the application of audio-visual media. In the pre-cycle, most students were in the